Rapid removal of nitrate from liquid dairy manure by cationic poly (vinyl alcohol-co-ethylene) nanofiber membrane. (15th March 2021) - Amaly, Noha; EL-Moghazy, Ahmed Y.; Sun, Gang; Pandey, Pramod
Abstract: Elevated levels of nitrate in surface water is a leading concern, which impacts human and animal health, and controlling it requires improved and sustainable methods capable of removing nitrate anions from source waste water to reduce nitrate anions transport to environment. In liquid dairy manure, nitrogen content can vary from 200 to 600 ppm and the transport of manure nitrogen into ambient water through hydrologic processes has a potential to exceed the maximum contaminant level limit (10 ppm) of nitrate nitrogen for regulated public water systems. Dairy manure is considered as a reservoir of nitrate. This research investigates on the determination of optimal designing of nanofiber membrane to remove nitrate anions from liquid dairy manure. A cationic poly (vinyl alcohol-co-ethylene) nanofiber membrane (EVOH) NFM was grafted via UV with 2-(methacryloyloxy) ethyl trimethylammonium chloride (DMAC) monomers. The adsorption efficiency of nitrate by the membrane was determined on liquid manure of dairy lagoons located in Central Valley of California. Initial nitrate concentrations in dairy manure varied from 75 to 100 ppm. Results showed that nitrate in dairy water was removed by 70% in 40 min. Tortuous structure and chemical stability of membrane resulted in nitrate dynamic binding capacity of 40 mg g −1 . Furthermore, it exhibits efficient reusability without significant changes in its performance using 0.5 M sodium hydroxide solution for nitrate desorption. Results showed that change in pH, and multi-anion conditions had limited effects on nitrate removal efficiency, and EVOH NFM can be a viable option to remove nitrate of liquid manure. This could be used for mitigating transport of excess nitrate from manure to environment. Overall, the results suggest that EVOH-g-DMAC NFM is efficient, low-cost (13 USD/m 3 ) and recyclable material for sustainable removal of nitrate from dairy manure wastewater without requiring any ionic strength or pH adjustment. Graphical abstract: Image 1 Highlights: Construction adsorptive nanofiber mat (NFM) for rapid nitrate adsorption. Cationic monomer grafted to (NFM) via UV-irradiation. High nitrate adsorption capacity 45 mg g −1 or 70% within 40 min with superb reusability. Dynamic adsorption, stability, economic cost and tensile strength meets industrial demands.